2007
DOI: 10.1111/j.1600-0404.2007.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological postmortem evaluation of BNCT for GBM

Abstract: Using a novel procedure for BPA infusion, BNCT achieves local control of GBM for minimum tumor doses as low as 15 wGy, allowing treatment with very low concomitant doses to surrounding healthy tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…The issue of so‐called ‘pseudoprogression’ as assessed in radiological images has been discussed in three recent publications with reference to progression in patients after TMZ chemotherapy (10, 18, 19). A similar false assessment of progression was also reported following a neuropathology examination at post‐mortem of seven brains from patients in the Studsvik BNCT study (15), where in all seven cases there was no evidence of GBM tumor at the original tumor site, contrary to radiological reports. In five cases there was no tumor found anywhere in the brain, despite reported progression based on radiological images.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The issue of so‐called ‘pseudoprogression’ as assessed in radiological images has been discussed in three recent publications with reference to progression in patients after TMZ chemotherapy (10, 18, 19). A similar false assessment of progression was also reported following a neuropathology examination at post‐mortem of seven brains from patients in the Studsvik BNCT study (15), where in all seven cases there was no evidence of GBM tumor at the original tumor site, contrary to radiological reports. In five cases there was no tumor found anywhere in the brain, despite reported progression based on radiological images.…”
Section: Resultssupporting
confidence: 64%
“…Considering all these factors, the longer MST in the Studsvik study compared with that for the entire population in the BNL study, 17.7 months vs 12.8 months and, even more compelling, compared with that for the two‐field treatment group in the BNL study, 12.6 months, a difference of 5 months, is a good evidence for substantially better clinical efficacy with the prolonged infusion protocol used in the study at Studsvik. Improved clinical efficacy, with prolonged infusion, is also indicated by the fact that local control of the GBM tumor was achieved in the Studsvik study but not in the BNL study, as shown by the post‐mortem neuropathological examination of 7 and 12 brains from these two studies, respectively (15, 16).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with earlier studies, where BNCT was applied to primary GBM (3) (Henriksson et al., private communication), no clear correlation was found between the tumor doses and survival times. In view of the results of the post‐mortem pathology study, where local control of GBM was observed for minimum tumor doses as low as 15 Gy‐Eq (4), the present results indicate that the full clinical potential of BNCT with the prolonged infusion of BPA is achieved already at minimum tumor doses in the range 15–20 Gy‐Eq. It is important to note that tumor doses at this level are obtained with concomitant average brain doses below 3 Gy‐Eq and that, within our present knowledge, it is conceivable that even lower doses could be equally effective.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, within the dose range employed, survival was not correlated to the radiation dose, in agreement with the results from an earlier BNCT trial at Brookhaven (3). Results from a post‐mortem pathology study including seven of the patients treated within the Studsvik phase II trial showed that control of GBM at the original tumor site was achieved in all cases and over a wide range of radiation doses, including minimum tumor doses as low as 15 Gy‐Eq (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation